Composite bonding composition of drying agent special for brake and application of composite bonding composition

By using composite bonding compositions of elotite, concave and convex rods, silicon sol and rare earth mixtures in brake-specific desiccants, the problem of microcracks in the bonding interface structure of brake-specific desiccants is solved, and the stability of bonding performance and service life are improved.

CN119897060APending Publication Date: 2025-04-29SHANGHAI HANGZHONG IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411942482.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Under frequent and violent temperature changes, the bonding interface structure of the bonding components is prone to local microcracks, resulting in unstable bonding performance and reduced service life.

Method used

A composite bonding composition comprising elotite, concave and convex rods, silica sol and rare earth mixture is a mixture of nickel oxide, cobalt oxide and chromium trioxide. Through the combination of these components, a stable bonding matrix is ​​formed to inhibit the generation and expansion of microcracks.

Benefits of technology

Under frequent and violent temperature changes, the generation and expansion of microcracks in the bonding interface structure are effectively suppressed, the relatively stable bonding performance is maintained, and the service life of the brake-specific desiccant is improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of drying agents special for braking, and particularly discloses a composite bonding composition of a drying agent special for braking and application of the composite bonding composition. The invention relates to a composite bonding composition of a drying agent special for a brake. The composite bonding composition comprises the following components in parts by weight: 15-30 parts of halloysite; 65 to 85 parts of attapulgite; 1-5 parts of silica sol; 1.8-3 parts of a rare earth mixture; the rare earth mixture is a mixture of nickel oxide, cobalt oxide and chromium sesquioxide. The composite bonding composition of the drying agent special for the brake can have a good restraining effect on formation and extension of microcracks in a frequent and violent temperature change environment, stable bonding performance can be kept, and the service life of the drying agent special for the brake is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of special desiccants for brakes, and more specifically, to a composite adhesive composition of a special desiccant for brakes and its application. Background Art

[0002] Special desiccant for brakes has the characteristics of high moisture absorption rate, fast moisture absorption speed and strong adsorption capacity. It can effectively absorb moisture in the air, prevent the formation of bubbles after moisture evaporation, and avoid damage to automobile brake parts due to moisture corrosion, thereby ensuring the safety and service life of the car. It is a common automotive accessory and plays an important role in the automobile braking system.

[0003] At present, natural zeolite, attapulgite, vermiculite, clay, apatite, calcium chloride, magnesium sulfate, activated alumina, borax and other raw materials are usually used, and these raw materials are mixed according to a certain weight ratio, and through a specific preparation process, such as mixing, ball rolling, drying, roasting, sieve dispersion heat and vacuum packaging, etc., the brake desiccant is finally obtained. Among them, some components act as adhesives. Through the molding process of the brake desiccant, the various components of the brake desiccant are firmly combined together to form a stable overall structure, which can better withstand the pressure and friction during use, thereby providing a more reliable effect during the application process.

[0004] With regard to the above-mentioned related technologies, the inventors believe that if the brake desiccant is subjected to frequent and drastic temperature changes during use, it will often lead to the inevitable appearance of local microcracks in the bonding interface structure formed by the adhesive components, and the stress caused by pressure and friction will further cause the expansion of microcracks. At this time, the adhesive components will find it difficult to maintain relatively stable bonding properties, which will greatly reduce the service life of the brake desiccant.

[0005] Therefore, it is urgent to propose a solution to solve the above technical problems. Summary of the invention

[0006] In order to prevent the adhesive components in the special desiccant for brakes from developing local microcracks when subjected to frequent and drastic temperature changes, and to effectively inhibit the expansion of their own microcracks and maintain relatively stable adhesive properties, thereby increasing the service life of the special desiccant for brakes, the present application provides a composite adhesive composition and application of a special desiccant for brakes.

[0007] In the first aspect, the present application provides a composite adhesive composition of a brake-specific desiccant, which adopts the following technical solution: A composite adhesive composition of a special desiccant for brakes, comprising the following components in parts by weight: Halloysite 15-30 parts; 65-85 parts of attapulgite; 1-5 parts of silica sol; 1.8-3 parts of rare earth mixture; The rare earth mixture is a mixture of nickel oxide, cobalt oxide and chromium trioxide.

[0008] By adopting the above technical scheme, attapulgite is a natural hydrated magnesium aluminum silicate with a unique three-dimensional spatial chain structure and a special needle and rod-shaped crystal structure. As the main raw material of the composite adhesive composition, it can bring higher mechanical strength and lower wear after application; silica sol is a colloid formed by dispersing silica colloid particles in a medium. During the application of the composite adhesive composition, these colloid particles can be connected to each other to form a spatial network structure, which has a better bonding effect; halloysite is a natural mineral with rich pore structure and good dispersibility, has the potential to enhance bonding strength, can effectively improve the physical properties of the adhesive, and make it have better wear resistance, heat resistance and cold resistance, thereby improving the bonding effect; and when attapulgite, silica sol and halloysite are mixed for use, a relatively stable and excellent bonding matrix can be formed.

[0009] At the same time, the composite adhesive composition also uses a rare earth mixture, which utilizes the high ductility and toughness of nickel, the mechanical property improvement and high temperature resistance of cobalt, and the structural reinforcement and wear resistance of chromium. Through the combination of the three, in the environment of frequent and drastic temperature changes, the microcracks in the bonding interface structure formed by the application of the composite adhesive composition can be effectively suppressed, and the extension of the microcracks can also be strongly contained, thereby significantly improving the effect of the composite adhesive composition of the brake desiccant. Moreover, the rare earth mixture and halloysite can also bring a more outstanding coordination effect. Through the load of part of the rare earth mixture in the halloysite pore structure, the composite adhesive composition can make the bonding interface structure formed more uniform and tight when applied, and show a higher tolerance to the microcracks caused by frequent and drastic temperature changes, thereby maintaining a relatively stable bonding performance and improving the service life of the brake desiccant.

[0010] Preferably, the weight ratio of nickel oxide, cobalt oxide and chromium oxide in the rare earth mixture is (3-5):(1.8-2.5):1.

[0011] By adopting the above technical scheme, the nickel oxide, cobalt oxide and chromium trioxide in the above weight ratio have better synergistic coordination with each other when used to form a rare earth mixture, and the temperature change resistance of the bonding interface structure formed by the composite adhesive composition is significantly improved, thereby effectively curbing the formation and expansion of microcracks, thereby ensuring that the composite adhesive composition can maintain excellent bonding performance under frequent and drastic temperature changes.

[0012] Preferably, the weight ratio of nickel oxide, cobalt oxide and chromium oxide in the rare earth mixture is 4.5:2:1.

[0013] By adopting the above technical solution, the nickel oxide, cobalt oxide and chromium oxide in the above weight ratio can bring better corresponding effects in actual application, and the obtained composite adhesive composition can also show better application effect in an environment with frequent and drastic temperature changes.

[0014] Preferably, the weight ratio of the halloysite to the rare earth mixture is 8:1.

[0015] By adopting the above technical scheme, when the halloysite and rare earth mixture in the above proportion are mixed and applied, the halloysite shows a better loading effect on the rare earth mixture, and through the dispersibility of halloysite, the rare earth mixture can fully act on the bonding matrix formed by the mixture of attapulgite, silica sol and halloysite, and then show a better effect on the bonding interface structure formed by the composite adhesive composition, which is conducive to the halloysite and rare earth mixture to exert a significant coordination effect, and obtain a composite adhesive composition with stable and excellent application quality.

[0016] Preferably, 1-1.5 parts by weight of a functional additive is added to the component, wherein the functional additive is composed of multi-walled carbon nanotubes and lanthanum oxide, and the weight ratio of the multi-walled carbon nanotubes to lanthanum oxide is 1:(1.2-1.6).

[0017] By adopting the above technical scheme, the introduction of lanthanum can improve the stability of the bonding interface structure formed by the composite adhesive composition and prevent it from changing under high temperature or specific environment; the multi-walled carbon nanotubes have excellent thermal stability and strong toughness, which can bring about the improvement of temperature change resistance and microcrack resistance; at the same time, in the application process of the composite adhesive combination, the multi-walled carbon nanotubes can form a stable hybrid structure with halloysite under the action of lanthanum oxide, which has a better inhibitory effect on the formation and expansion of microcracks, and can bring about a significant improvement in the bonding stability of the composite adhesive composition in an environment of frequent and drastic temperature changes.

[0018] Preferably, the weight ratio of the multi-walled carbon nanotubes to lanthanum oxide is 1:1.4.

[0019] By adopting the above technical scheme, when the multi-walled carbon nanotubes and lanthanum oxide in the above weight ratio are used in combination, the composite effect brought by each other is better. Under the premise of sufficient interaction with halloysite, the formed hybrid structure can also be fully dispersed in the bonding matrix, thereby obtaining a composite bonding composition with better application bonding stability.

[0020] Preferably, the halloysite is modified before use, and the modification steps are as follows: S1, taking the halloysite raw material, placing it in anhydrous ethanol for heating and reflux treatment, adding stearic acid at a temperature of 75-85° C. and stirring for 40-60 minutes, cooling, filtering and drying to obtain pretreated halloysite; S2. Spraying an aqueous solution of a silane coupling agent on the surface of the pretreated halloysite, allowing it to stand for a while, and then drying it to obtain modified halloysite.

[0021] By adopting the above technical scheme and performing the above modification treatment on halloysite, the modified halloysite obtained has more excellent dispersibility, stability and compatibility, and can form a better loading effect on the rare earth mixture, which can not only improve the compactness of the bonding matrix formed by attapulgite, silica sol and halloysite, but also enable the rare earth mixture to play a more excellent role in the above bonding matrix, thereby further improving the bonding stability of the composite bonding composition in an environment of frequent and drastic temperature changes.

[0022] Preferably, in step S1, the amount of stearic acid used is 4-6% of the mass of the halloysite raw material; in step S2, the amount of silane coupling agent used is 0.5-2% of the mass of the pretreated halloysite.

[0023] By adopting the above technical scheme, in the preparation of modified halloysite, the amount of the above raw materials is selected in each step of the operation, so that the modified halloysite obtained can show strong adaptability with attapulgite and silica sol, and the coordination effect with the rare earth mixture is also better, thereby making the bonding stability of the composite adhesive composition after application in an environment of frequent and drastic temperature changes also relatively excellent.

[0024] In a second aspect, the present application provides a composite adhesive composition of a brake-specific desiccant for use in an automobile braking system.

[0025] By adopting the above technical scheme, the composite adhesive composition firmly combines the various component raw materials of the special brake desiccant during the molding process of the special brake desiccant to form a stable overall structure, which can effectively reduce the dew point of compressed air, prevent freezing corrosion, and protect the air brake system from blockage and corrosion problems caused by moisture, thereby ensuring the normal operation of the automobile brake system and the safe driving of the automobile.

[0026] In summary, this application has the following beneficial effects: 1. The present application uses a rare earth mixture obtained by mixing nickel oxide, cobalt oxide and chromium trioxide, which can effectively inhibit the generation of microcracks in the bonding interface structure formed by the application of the composite adhesive composition under frequent and drastic temperature changes, and also has a strong inhibitory effect on the expansion of microcracks, thereby significantly enhancing the expected effect of the composite adhesive composition of the brake special desiccant; 2. The functional additives composed of multi-walled carbon nanotubes and lanthanum oxide added in the present application can form a stable hybrid structure with halloysite, which has a better restraining effect on the formation and expansion of microcracks, and can significantly improve the bonding stability of the composite adhesive composition under frequent and drastic temperature changes; 3. The present application modifies halloysite, which not only makes the modified halloysite show stronger compatibility with attapulgite and silica sol, but also can form a better loading effect on the rare earth mixture, so that the rare earth mixture can play a more excellent role in the bonding matrix, thereby improving the bonding stability of the composite bonding composition in an environment with frequent and drastic temperature changes. DETAILED DESCRIPTION

[0027] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.

[0028] Unless otherwise specified, the raw materials used in the preparation examples, embodiments and comparative examples of the present application are commercially available: Halloysite was purchased from Shijiazhuang Borui Building Materials Co., Ltd., with a specification of 325 mesh; The attapulgite was purchased from Mingguang Feizhou New Materials Co., Ltd., with a specification of 200 mesh; Silica sol was purchased from Jinan Rongzheng Chemical Co., Ltd., with an active ingredient content of 30% and a particle size of 200 mesh; Multi-walled carbon nanotubes were purchased from Guangzhou Hongwu Material Technology Co., Ltd., with the brand name HWP-C930; Stearic acid was purchased from Sven Stearic Acid SA1801; The silane coupling agent is KH-550 type silane coupling agent; The pore size of the synthetic zeolite was selected from 4A, which was purchased from Zhengzhou Chaorong Nanomaterials Co., Ltd.

[0029] Preparation examples of raw materials and / or intermediates Preparation Example 1 A modified halloysite is obtained by the following modification treatment steps: S1, taking the halloysite raw material and placing it in 5 times the volume of anhydrous ethanol for heating and reflux treatment, adding stearic acid at a temperature of 75-85° C. (preferably 80° C. in this preparation example) and stirring at 300 r / min for 40-60 min (preferably 50 min in this preparation example), cooling, filtering and drying to obtain pretreated halloysite; S2. Spray a 15% aqueous solution of silane coupling agent on the surface of the pretreated halloysite, let it stand for 30 minutes and then dry it to obtain the modified halloysite.

[0030] Note: In step S1, the amount of stearic acid used is 5% of the mass of the halloysite raw material; in step S2, the amount of silane coupling agent used is 1.25% of the mass of the pretreated halloysite.

[0031] Preparation Example 2 A modified halloysite is different from Preparation Example 1 in that in step S1, the amount of stearic acid used is 4% of the mass of the halloysite raw material; in step S2, the amount of silane coupling agent used is 0.5% of the mass of the pretreated halloysite.

[0032] Preparation Example 3 A modified halloysite is different from Preparation Example 1 in that in step S1, the amount of stearic acid used is 6% of the mass of the halloysite raw material; in step S2, the amount of silane coupling agent used is 2% of the mass of the pretreated halloysite. Example

[0033] Examples 1-3 A composite adhesive composition of a special desiccant for brakes, the components and their corresponding weights are shown in Table 1, the rare earth mixture is a mixture of nickel oxide, cobalt oxide and chromium trioxide, and the weight ratio of nickel oxide, cobalt oxide and chromium trioxide is 4.5:2:1.

[0034] Table 1 Components and their corresponding weights in Examples 1-3 (kg / portion) Components Example 1 Example 2 Example 3 Halloysite 22.5 15 30 Attapulgite 75 65 85 Silica Sol 3 1 5 Rare earth mixture 2.4 1.8 3 Example 4 A composite adhesive composition of a special desiccant for brakes, which is different from Example 1 in that the weight ratio of nickel oxide, cobalt oxide and chromium oxide in the rare earth mixture is 4:2.15:1.

[0035] Example 5 A composite adhesive composition of a special desiccant for brakes, which is different from Example 1 in that the weight ratio of nickel oxide, cobalt oxide and chromium oxide in the rare earth mixture is 3:1.8:1.

[0036] Example 6 A composite adhesive composition of a special desiccant for brakes, which is different from Example 1 in that the weight ratio of nickel oxide, cobalt oxide and chromium oxide in the rare earth mixture is 5:2.5:1.

[0037] Example 7 A composite adhesive composition of a special desiccant for brakes, which is different from Example 1 in that 1.25 parts by weight of a functional additive is also added to the component, the functional additive is composed of multi-walled carbon nanotubes and lanthanum oxide, and the weight ratio of the multi-walled carbon nanotubes to lanthanum oxide is 1:1.4.

[0038] Example 8 A composite adhesive composition of a special desiccant for brakes, which is different from Example 7 in that the added weight portion of the functional additive is 1 part.

[0039] Example 9 A composite adhesive composition of a special desiccant for brakes, which is different from Example 7 in that the added weight portion of the functional additive is 1.5 parts.

[0040] Example 10 A composite adhesive composition of a special desiccant for brakes, which is different from Example 7 in that the weight ratio of multi-walled carbon nanotubes to lanthanum oxide is 1:1.2.

[0041] Embodiment 11 A composite adhesive composition of a special desiccant for brakes, which is different from Example 7 in that the weight ratio of multi-walled carbon nanotubes to lanthanum oxide is 1:1.6.

[0042] Example 12 A composite adhesive composition of a special desiccant for brakes, which is different from Example 7 in that the functional additive does not contain multi-walled carbon nanotubes.

[0043] Embodiment 13 A composite adhesive composition of a special desiccant for brakes, which is different from Example 7 in that the functional additive does not contain lanthanum oxide.

[0044] Embodiment 14 A composite adhesive composition of a special desiccant for brakes, which is different from Example 1 in that the mass of halloysite is replaced by modified halloysite, and the modified halloysite is obtained in Preparation Example 1.

[0045] Embodiment 15 A composite adhesive composition of a special desiccant for brakes, which is different from Example 14 in that the modified halloysite is obtained in Preparation Example 2.

[0046] Example 16 A composite adhesive composition of a special desiccant for brakes, which is different from Example 14 in that the modified halloysite is obtained in Preparation Example 3.

[0047] Comparative Example Comparative Example 1 A composite adhesive composition of a special desiccant for brakes, which is different from Example 1 in that nickel oxide and chromium trioxide are not used in the rare earth mixture.

[0048] Comparative Example 2 A composite adhesive composition of a special desiccant for brakes, which is different from Example 1 in that cobalt oxide and chromium trioxide are not used in the rare earth mixture.

[0049] Comparative Example 3 A composite adhesive composition of a special desiccant for brakes, which is different from Example 1 in that nickel oxide and cobalt oxide are not used in the rare earth mixture.

[0050] Comparative Example 4 A composite adhesive composition of a special desiccant for brakes, which is different from Example 1 in that nickel oxide is not used in the rare earth mixture.

[0051] Comparative Example 5 A composite adhesive composition of a special desiccant for brakes, which is different from Example 1 in that cobalt oxide is not used in the rare earth mixture.

[0052] Comparative Example 6 A composite adhesive composition of a special desiccant for brakes, which is different from Example 1 in that chromium trioxide is not used in the rare earth mixture.

[0053] Comparative Example 7 A composite adhesive composition of a special desiccant for brakes, which is different from Example 1 in that no rare earth mixture is used in the composition.

[0054] Comparative Example 8 A composite adhesive composition of a special desiccant for brakes, which is different from Example 1 in that halloysite is not used in the composition.

[0055] Comparative Example 9 A composite adhesive composition of a special desiccant for brakes, which is different from Example 1 in that halloysite and rare earth mixture are not used in the composition.

[0056] Comparative Example 10 A composite adhesive composition of a special desiccant for brakes, which is different from Example 7 in that halloysite is not used in the composition.

[0057] Application Examples A molecular sieve desiccant for a brake system is prepared by the following method: Step 1: Mix the composite adhesive composition of synthetic zeolite and brake-specific desiccant in a mass ratio of 70:3, perform ball rolling treatment, and obtain spherical particles with a particle diameter of 1.7 mm after vibration screening; Step 2: drying the spherical pellets in five zones at 60°C, 70°C, 80°C, 90°C and 100°C in sequence, with the residence time in each drying zone being 10 minutes; Step 3, the dried spherical pellets are sequentially subjected to eight-zone roasting treatments at 110°C, 210°C, 310°C, 420°C, 530°C, 640°C, 750°C, and 850°C, and the residence time in each roasting zone is 10min, 5min, 5min, 5min, 8min, 8min, 8min, and 20min, respectively; Step 4: After the spherical material obtained after calcination is heat-dissipated, it is sieved to obtain a molecular sieve desiccant for a brake system with a diameter of 1.7 mm.

[0058] The composite adhesive composition using the special desiccant for brakes obtained in Examples 1-16 and applied in the above-mentioned manner are recorded as Application Examples 1-16; the composite adhesive composition using the special desiccant for brakes obtained in Comparative Examples 1-10 and applied in the above-mentioned manner are recorded as Application Examples 17-26.

[0059] Performance test sample: The molecular sieve desiccant for the brake system obtained in Application Example 1-26 was used as test sample 1-26.

[0060] Test method: (1) Use a molecular sieve crushing strength tester to test the compressive strength of test samples 1-26. Each sample is tested three times, and the average value is taken as the initial compressive strength of each sample, which is recorded as A1; (2) Place test samples 1-26 in a high and low temperature alternating test chamber with an initial temperature of 25°C. First, heat it to 150°C at 3°C / min, then cool it to -40°C at 1.5°C / min, and then heat it to 25°C at 2°C / min. This is recorded as one cycle. After 20 cycles, take out the test samples and test them using a molecular sieve crushing strength tester. Each sample is tested three times, and the average value is taken as the compressive strength of each sample after the temperature change test, which is recorded as A2; (3) Calculate the compressive strength loss rate of each test sample after the temperature change test, compressive strength loss rate = (A1-A2) / A1, and record it in Table 2 accordingly.

[0061] Table 2 Application test results of Examples 1-16 and Comparative Examples 1-10 Composite adhesive composition Compressive strength loss rate (%) Example 1 3.56 Example 2 3.78 Example 3 3.67 Example 4 3.61 Example 5 3.72 Example 6 3.75 Example 7 2.17 Example 8 2.28 Example 9 2.21 Example 10 2.26 Embodiment 11 2.24 Example 12 3.15 Embodiment 13 3.04 Embodiment 14 2.67 Embodiment 15 2.73 Example 16 2.71 Comparative Example 1 7.50 Comparative Example 2 7.28 Comparative Example 3 7.36 Comparative Example 4 6.15 Comparative Example 5 5.93 Comparative Example 6 6.07 Comparative Example 7 8.71 Comparative Example 8 5.18 Comparative Example 9 12.14 Comparative Example 10 6.15 It can be seen from Examples 1-3 and Comparative Examples 1-7 and Table 2 that by using a rare earth mixture obtained by mixing nickel oxide, cobalt oxide and chromium trioxide, the composite adhesive composition can maintain good stability after application even if it is subjected to frequent and drastic temperature changes, and the compressive strength loss rate obtained by testing is also low, indicating that the application effect of the desiccant is also more excellent and stable; while if any one or two of nickel oxide, cobalt oxide and chromium trioxide are used, although the corresponding effect can be improved, the improvement is very limited, and the corresponding effects are simply superimposed on each other, which is far less than the excellent effect brought by the compounding of the three. Combined with Comparative Examples 8-9 and Table 2, it can be seen that if rare earth mixture and halloysite are not used, the compressive strength loss rate obtained by the test is significantly larger. On this basis, using any one of the rare earth mixture and halloysite can bring a certain improvement effect, but the sum of the improvement effects brought by each of them is far less than the excellent effect brought by the combination of the two. It can be seen that the combination of rare earth mixture and halloysite can bring an outstanding effect of 1+1>2 for the technical problem to be solved by this application.

[0062] It can be seen from Example 1 and Examples 4-6 and Table 2 that when the weight ratio of nickel oxide, cobalt oxide and chromium trioxide in the rare earth mixture is (3-5):(1.8-2.5):1, it can achieve relatively excellent and stable application effects, and can ensure that the composite adhesive composition can maintain good bonding performance under frequent and drastic temperature changes, thereby making the compressive strength loss rate obtained by the above test lower; among them, when the weight ratio of nickel oxide, cobalt oxide and chromium trioxide is 4.5:2:1, the corresponding effect brought by the rare earth mixture is better.

[0063] It can be seen from Example 1 and Example 7-11 and Table 2 that by adding a functional additive composed of multi-walled carbon nanotubes and lanthanum oxide, the bonding stability of the composite adhesive composition under frequent and drastic temperature changes can be further improved, thereby further reducing the compressive strength loss rate obtained by the test; wherein, when the weight ratio of multi-walled carbon nanotubes and lanthanum oxide is 1:1.4, the application effect brought by the functional additive is better. It can be seen from Example 12-13 and Table 2 that if any one of multi-walled carbon nanotubes and lanthanum oxide is used alone as a functional additive, the effect brought is limited, and is far less than the excellent effect brought by the compounding of the two. It can be seen from Comparative Example 8 and then Comparative Example 10 and Table 2 that if halloysite is missing, it is found that the effect brought by the functional additive will be greatly discounted, which shows that the excellent improvement effect brought by the functional additive is inseparable from halloysite, and the two have an inseparable coordination mechanism.

[0064] It can be seen from Example 1 and Examples 14-16 and Table 2 that by modifying the halloysite, the bonding stability of the composite adhesive composition in an environment of frequent and drastic temperature changes can be improved, thereby further reducing the compressive strength loss rate obtained in the test, indicating that the modified halloysite has better compatibility with attapulgite and silica sol, and also better coordination with the rare earth mixture.

[0065] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.

Claims

1. A composite adhesive composition of a brake-specific desiccant, characterized in that: Contains the following components in parts by weight: Halloysite 15-30 parts; 65-85 parts of attapulgite; 1-5 parts of silica sol; 1.8-3 parts of rare earth mixture; The rare earth mixture is a mixture of nickel oxide, cobalt oxide and chromium trioxide.

2. The composite adhesive composition of the brake-specific desiccant according to claim 1, characterized in that: The weight ratio of nickel oxide, cobalt oxide and chromium oxide in the rare earth mixture is (3-5): (1.8-2.5):

1.

3. The composite adhesive composition of the brake-specific desiccant according to claim 2, characterized in that: The weight ratio of nickel oxide, cobalt oxide and chromium oxide in the rare earth mixture is 4.5:2:

1.

4. The composite adhesive composition of the brake-specific desiccant according to claim 3, characterized in that: The weight ratio of the halloysite to the rare earth mixture is 8:

1.

5. The composite adhesive composition of the special desiccant for brakes according to claim 1, characterized in that: The components are also added with 1-1.5 parts by weight of a functional additive, which is composed of multi-walled carbon nanotubes and lanthanum oxide, and the weight ratio of the multi-walled carbon nanotubes to lanthanum oxide is 1:(1.2-1.6).

6. The composite adhesive composition of the brake-specific desiccant according to claim 5, characterized in that: The weight ratio of the multi-walled carbon nanotubes to lanthanum oxide is 1:1.

4.

7. The composite adhesive composition of the brake-specific desiccant according to claim 1, characterized in that: The halloysite is modified before use, and the modification steps are as follows: S1, taking the halloysite raw material, placing it in anhydrous ethanol for heating and reflux treatment, adding stearic acid at a temperature of 75-85° C. and stirring for 40-60 minutes, cooling, filtering and drying to obtain pretreated halloysite; S2. Spraying an aqueous solution of a silane coupling agent on the surface of the pretreated halloysite, allowing it to stand for a while, and then drying it to obtain modified halloysite.

8. The composite adhesive composition of the brake-specific desiccant according to claim 7, characterized in that: In step S1, the amount of stearic acid used is 4-6% of the mass of the halloysite raw material; in step S2, the amount of silane coupling agent used is 0.5-2% of the mass of the pretreated halloysite.

9. Use of the composite adhesive composition of the brake-specific desiccant according to any one of claims 1 to 8 in an automobile braking system.